The YoungFitT project: Study protocol for a randomized mixed-methods trial of physical exercise and mind-body interventions, with or without virtual reality, in university students - Samira Rostami; Adrià Bermudo-Gallaguet; Neus Camins-Vila; Blai Ferrer-Uris; Albert Busquets; Mireia Ribera; Laura Coll; Jaime Gallego Vila; Ramon Oliva Martínez; Mel Slater; Gustavo Garcia Diez; Nazareth Perales Castellanos; et al. (PLoS ONE, 2025)
Background Mental health issues among young university students have increased in recent years, driven by academic stress and sedentary lifestyles. The YoungFitT Project aims to explore well-being strategies and the psychobiological mechanisms behind their effects on university students. The project includes two studies: the first evaluates the effectiveness of High-Intensity Functional Training (HIFT), Mindfulness-Based Stress Reduction (MBSR), and Qigong (QG) on psychological well-being and cognitive functions, and also explores whether socio-demographic, mental (mindful thinking, sleep quality), physical (physical fitness, physical activity), physiological (heart rate variability), and biological (microbiota) factors mediate or moderate intervention effects on university students. Given that immersive virtual reality (VR) can enhance adherence and provide additional benefits, the second study will explore the feasibility and efficacy of HIFT-VR, MBSR-VR, and QG-VR on university students’ psychological well-being and cognitive functions. Methods Two mixed-methods randomized controlled trials will be conducted. In Study 1, participants will be randomly assigned to one of three groups (HIFT, MBSR, QG) using a 1:1:1 ratio. Psychological, cognitive, physical, physiological, and biological measures will be evaluated two weeks before and after the interventions. The interventions include three weekly sessions for 12 weeks. Subsequently, a follow-up will be conducted 12 weeks after the intervention to assess psychological well-being. Study 2 is a proof-of-concept study in which VR interventions will be co-designed with input from university students and professionals. Twelve participants from each study will also complete semi-structured interviews to explore their experiences and perceived impact. Discussion The proposed interventions are expected to produce differential effects on psychological well-being and cognitive function. VR environments may enhance adherence and offer added benefits over conventional training. Findings will inform effective, personalized strategies for the mental and physical health of university youth. Trial registration www.ClinicalTrials.gov, identifier NCT06406283; Registration date: 2024/05/06.